KEBIJAKAN PENANAMAN MODAL ASING (PMA) DAN DAMPAK KEDAULATAN BANGSA - Sirwanto Sirwanto (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: Indonesia in carrying out development requires a very large capital, because of the vast territory and a very large population. But in fact Indonesia has the potential of natural resources (SDA) which is very large too, if the potence can be managed solely for the interests of the people as mandated in article 33 of the 1945 Constitution of the Republic of Indonesia. To accelerate the management of these natural resources, the government need investment both from within the country, and from foreign investment (PMA). Because domestic investment is relatively small compared to the cost of managing natural resources, while this nation must catch up with other nations, PMA is a very possible alternative to this, even though it is very risky for foreign intervention to sovereignty of the country. For this reason, the government must make clear and impartial regulations, consistent with these regulations and have a good political will, so that problems can be overcome and the sovereignty of the nation and state is maintained, so that this nation will advance equally with the nations other majalis nation.Keywords: PMA, Government, Sovereignty and investment